My neighbour, the subject of civilisation - Lorens Holm (lo Squaderno, 2023)
In Frost’s poem, two neighbours pace their wall, replacing the stones that have toppled. Each to their own side. They do it every Spring. Like a ritual. Frost is critical of the wall, in a neighbourly way, because his neighbour wants the wall and he doesn’t see the point. The poem recalls the spectre of the American range wars of the 1890s, between cattlemen and farmers. They were excessively violent, largely because of the unregulated nature of the terrain in which their conflicts of interest were staged.